Africa's unique genetic resources - cattle - International Livestock Research Institute (International Livestock Research Institute, 2020)
LRI scientists use ‘genomic time travel’ to discover how African cattle became so diverse and adaptable. The researchers uncovered a treasure trove of genetic traits resulting from centuries of methodical breeding work by traditional pastoralist herders. “It’s important to understand that livestock breeding has long played a vital role in sustaining the health and wealth of African communities,” said ILRI Director General Jimmy Smith. “The focus on breeding for resilience that guided past efforts provides a touchstone for future work to chart a sustainable path for livestock production in sub-Saharan Africa.”